Konsep Patogenesis Sepsis pada Ventilator Associated Pneumonia di Intensive Care Unit - Febyan, Febyan; Lardo, Soroy (Majalah Kedokteran Indonesia, 2018)
Severe sepsis is sepsis with one or more organ dysfunction. One of the causes of sepsis in Intensive Care Unit (ICU) is Hospital-Acquired Pneumonia (HAP). HAP occurs 5-10 cases per 1000 patients on mechanical ventilation. Ventilator Associated Pneumonia (VAP) is predominantly caused by Pseudomonas aeruginosa. Several important factors in the pathogenesis of VAP are barrier to Na+-K+-Cl– transporter-1 (NKCC1), endotracheal tube device without antibiofilm. VAP can be prevented by oral hygiene, endotracheal tube device made from antibiofilm, head up 30 degrees, evaluation of cough ability, swallowing function